Analisis dan Perancangan Sistem Informasi Koperasi Mahasiswa Berbasis Web Pada Koperasi Mahasiswa - Togatorop, Ester Debora; Hariadi, Bambang; Amelia, Tan (Jurnal Sistem Informasi Universitas Dinamika, 2020)
The student cooperative (Kopma) is a business entity managed by students that offers entrepreneurial experience to students. Kopma has many activities including purchasing, sales, consignation, maintenance scheduling, Business Profit Calculation (SHU). Problems faced by Kopma include the process of scheduling guarding, selling, purchasing, purchasing, and consignment transactions carried out manually so that when calculating the contribution of members often experience problems, because waiting for the recap of each district that resulted in the calculation of SHU for Rapat Anggota Tahunan (RAT) often experience recording errors reporting. Of the problems faced by Kopma, the solution provided is the design and analysis of Kopma information systems. Where the analysis and analysis of this information system produces a Kopma information system that can integrate reports from each Kopma operational activity. The results of the analysis and design of the Kopma information system as a reference for the implementation of the system so that the workmanship is in accordance with the analysis and design documents of the Kopma information system. The results of these documents are in accordance with user requirements based on the results of usability testing conducted to AKMS representatives where 5 testers can easily use the Kopma information system design prototype. the advice given for the next development of the Kopma information system prototype can be continued until the system implementation stage.